EFFECTS OF ESSENTIAL SENSORY-MOTOR INTERVENTION PROGRAM (ISME) IN THE MOTOR REHABILITATION OF PREMATURE NEWBORNS WITH NEUROMOTOR DYSFUNCTIONS (Fiep Bulletin - online, 2014)
Introduction: Thirty percent of premature newborns that need special care and who undergo NICU are at risk of developing brain injuries. Purpose: This study investigated the effects of an immediate intervention program compared to the effects of the same program applied at a later stage, in premature newborns with neuromotor dysfunctions due to hypoxicischemic syndrome. The Denver II scale provided the referential points for analysis of the neurodevelopment motor stage gains achieved with the ISME program. Methods: Forty preterm babies presented signs of Central Nervous System lesions at the Dubowitz tests. The subjects were divided into two groups: the immediate intervention (n=20), and the later intervention (n=20). The pre and post program data were studied through qualitative analysis and non-parametric statistics (Mann/Whitney test), considering the acquired motor stages. Variance analysis revealed a significant statistical difference between data from both groups in all trimesters of the program's application, with p
Keywords: Prematurity; Hypoxic-Ischemic Syndrome; Early Intervention Program